Simulation and Experimental Study on Vibration and Noise Characteristics of the Main Reducer of an Electric Drive Axle - Cui Yue; Tian Shaopeng; Zou Lin; Wang Xinqiang (Jixie chuandong)
In this study, a simulation model of the two-stage helical gear pair-rotor-bearing of the main reducer is developed by Adams software. The simulation results show that the noise mainly comes from the resonance of the system and the contribution of the high-speed gear pair is large when the speed is in the range of 0~3 000 r/min. Furthermore, the vibration test of the main reducer and the real vehicle noise test are also conducted. The test results show that the noise of the main reducer increases obviously when the input speed is 2 138.67 r/min, and the corresponding meshing frequency of the gear pair is 605.96 Hz, verifying the simulation results. Finally, the effect of bearing stiffness on the resonance speed distribution is studied, and the optimization measures of the structural stiffness of the system are proposed. After optimization, the vibration amplitude decreases significantly when the speed is in the range of 1 400~2 200 r/min, and the resonance speed shifts to a higher speed. The relative errors between the test results and simulation analysis results are less than 5%, which verifies the Adams simulation results and the optimization measures, and provides some reference for shortening the development cycle of the electric drive axle main reducer and saving research and development costs.